'Knocking-fingers' chest compression technique in infant cardiac arrest: single-rescuer manikin study. (August 2019) - Jung, Woo Jin; Hwang, Sung Oh; Kim, Hyung Il; Cha, Yong Sung; Kim, Oh Hyun; Kim, Hyun; Lee, Kang Hyun; Cha, Kyoung-Chul
Abstract : Objective: We designed a new chest compression technique, the 'knocking-fingers' chest compression (KF) technique, for a single rescuer in infant cardiac arrest. We compared the effectiveness and feasibility between the KF technique and the two-finger (TF) and two-thumb encircling hands (TT) techniques. Participants and methods: A prospective, randomized, crossover study was carried out to compare the quality of chest compression and ventilation between the KF, TF, and TT techniques using a 30: 2 compression-to-ventilation ratio and mouth-to-mouth ventilation. The area of chest compression, finger(s) pain, and fatigability were measured to compare safety and feasibility. Results: The total frequency of chest compression for 5 min was the highest with the KF technique, followed by the TF and TT techniques. The total frequency of ventilation for 5 min was higher with the KF and TF techniques compared with the TT technique. The total hands-off time was the shortest with the KF technique, followed by the TF and TT techniques. The area of chest compression was the smallest in KF technique. Participants complained of severe finger pain and high fatigability in TF technique. Conclusion: The single-rescuer KF chest compression technique is an effective alternative to the TF or TT techniques for infant cardiac arrest. Abstract : Supplemental Digital Content is available in the text.